Pengaruh Motivasi Kerja Karyawan Terhadap Kinerja Karyawan di Royal Tulip Gunung Geulis Resort and Golf - Dwi Putri, Aggy Lestari; Simanihuruk, Maidar (Tourism Scientific Journal, 2023)
The purpose of this study is to look at employee work motivation and its link to employee performance at the Royal Tulip Gunung Geulis Resort & Golf. Apprentice employees are different from employees and daily workers. Where these apprentice employees are not owned by all hotels. The quantitative descriptive approach was utilized, with a questionnaire disseminated via Google Form and analyzed using SPSS. The study's findings indicate that employee work motivation at the resort is fairly high, with a significant value less than the necessary R2 value. The association between job motivation and employee performance is modest. Work motivation influences employee performance by 34%, whereas other variables not investigated in this study affect employee performance by 66%. Finally, employee job motivation impacts employee performance at the Royal Tulip Gunung Geulis Resort & Golf, but other elements also play a role.